2020
DOI: 10.1123/ijspp.2019-0621
|View full text |Cite
|
Sign up to set email alerts
|

Field-Derived Power–Duration Variables to Predict Cycling Time-Trial Performance

Abstract: Purpose: To evaluate the predictive validity of critical power (CP) and the work above CP (W′) on cycling performance (mean power during a 20-min time trial; TT20). Methods: On 3 separate days, 10 male cyclists completed a TT20 and 3 CP and W′ prediction trials of 1, 4, and 10 min and 2, 7, and 12 min in field conditions. CP and W′ Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 24 publications
1
17
1
Order By: Relevance
“…Good agreement between CP estimates derived from formal testing and MMP values has been reported (Leo et al 2020 , 2021a ; b ; Nimmerichter et al 2020 ; Quod et al 2010 ). While a good agreement between CP derived from formal testing and racing has been shown, the same cannot be confirmed for W ′.…”
Section: Agreement Between Modelled Power-duration Relationship and Mmp Valuesmentioning
confidence: 82%
See 3 more Smart Citations
“…Good agreement between CP estimates derived from formal testing and MMP values has been reported (Leo et al 2020 , 2021a ; b ; Nimmerichter et al 2020 ; Quod et al 2010 ). While a good agreement between CP derived from formal testing and racing has been shown, the same cannot be confirmed for W ′.…”
Section: Agreement Between Modelled Power-duration Relationship and Mmp Valuesmentioning
confidence: 82%
“…Unfortunately, this approach (i.e. comparing MMP against a pre-established theoretical power-duration relationship derived from prior formal testing) was only undertaken by a few research groups (Leo et al 2020 ; Leo et al 2021b ; Nimmerichter et al 2020 ; Quod et al 2010 ). However, all research has shown good to very good agreement between power output values from formal testing and MMP values.…”
Section: Methodological Approaches To Power Profilingmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 242 participants were involved in the records (199 males, 43 females, mean ± SD: age = 29.1 ± 5.9 years). Ten of the studies included men and women [13][14][15][16][17][18][19][20][21][22], while the rest included only men [8,[23][24][25][26][27][28][29][30][31][32]. The inclusion criteria for participants were defined as trained and experienced athletes.…”
Section: Characteristics Of the Participantsmentioning
confidence: 99%